Teaching motivation of physical education teachers in middle schools. -A field study in some sample middle schools in M'sila province- - الأمين دشيشة (sports creativity, 2025)
Teaching motivation of physical education teachers in middle schools. ( A field study in some sample middle schools in M'sila province) The study questions: -What is the level of motivation of teaching physical education and sports teachers in education? - Are there differences in the level of motivation of teaching physical education and sports teachers due to a variable qualification (University, Institute of Technology)? - Are there differences in the level of motivation of teaching physical education and sports teachers due to a variable years of experience (less than 5years, from 5 years to 10 years, more than 10 years)? - Are there differences in the level of motivation of teaching physical education and sports teachers attributed the elderly.25 to 30 years, from 31 to 35 years, 36 years and above)?  The hypotheses of the study: * featuring Professors of Physical Education and Sports in the average education level of the average of the motivation to teach. * There are significant differences in the level of motivation of professors teaching physical education and sports due to a variable qualification, University, Institute of Technology). * There are significant differences in the level of motivation of professors teaching physical education and sports due to a variable years of experience (less than 5years, from 5 years to 10 years, more than 10 years). * There are significant differences in the level of motivation of professors teaching physical education and sports due to a variable age (from 25 to 30 years, from 31 to 35 years, 36 years and over)